PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE BERBASIS PANEL PERAGA SEBAGAI UPAYA MENINGKATKAN KOMPETENSI MAHASISWA PADA MATERI SISTEM PENGAPIAN MOBIL - Hadromi, Hadromi (Jurnal Penelitian Pendidikan, 2011)
The purpose of this study to develop a car ignition system media panel displays which can be a learning media in automobile ignition systems, and apply the learning cycle-based learning model panel displays the results of development as an effort to increase student competence in the material car ignition system. Classroom action research study (TOD) was started from the planning stage (action plan), implementation (implementation actions), observation, and reflection that followed re-planning if it is still encountered problems. Implementation of learning by applying the learning cycle model â5Eâ. Subjects were students taking courses in Automotive Electrical Prodi. Education Mechanical Engineering, while the object of research is, the application of learning cycle-based learning model viewer panel. Indicators of success of this study is at least more than 50% of participants learning to obtain the value 86 (A). The results showed that application of model-based panel LC displays in three cycles to reach the benchmark of success is as much as 61.55% of research participants learn to obtain a score of 86 to the upper (A). From these results, it is advisable to apply the learning in the LC model as upya pemebalajaran process to increase participantsâ understanding of learning in learning menguasmateri.